PENGARUH HANDOUT BERORIENTASI PENDEKATAN SAINTIFIK TERHADAP HASIL BELAJAR IPA-FISIKA SISWA KELAS IX SMP PERTIWI 2 PADANG - Giffi Febri Yeni; Amali Putra; Hufri Hufri (PILLAR OF PHYSICS EDUCATION, 2015)
This study aims to investigate the influence of Handout oriented scientific approach to science learning outcomes-physics class IX students of SMP Earth 2 Padang in the 1st half of the school year 2014/2015. The research is a "quasi experiment" with the draft "only randomized control group design. Sampling was done by using purposive sampling. Data research include learning outcomes in the cognitive, affective, and psychomotor. The research instrument in the form of a written test for cognitive learning outcomes, observation sheet for affective learning outcomes, and the scoring rubric for the assessment of psychomotor performance. Data analysis of learning outcomes in the cognitive, affective and psychomotor the experimental class is better than the control class. Conclusion of the study is the hypothesis that there is a significant effect of giving handouts oriented scientific approach to science learning outcomes-Physics Students junior class IX Earth 2 fields can be accepted at the 0.05 significance level.